Ontological Engineering Approach Towards Botnet Detection in Network Forensics - Kaur, Sukhdilpreet; Verma, Amandeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The abundance in the usage of Internet, in every arena of life from social to personal, commercial to domestic and other aspects of life as well, leads the rise in cybercrime at an upsetting speed. More illegal activities as a result of cyber crime, reason to tempts many network attacks and threats. Network forensics is the branch of fornesics that deals in the detection of network attacks. Botnet is one of the most common attacks, but hazardos. It is a network of hacked computers It involves the capturing, storing and then analysis of the network packets, in order to identify the source of the attack. Various methods based on this approach for botnet detection are suggested in literature but there is no generalized method to represent the basic methodology used by any of the botnet detection method. With such guidelines, the comparison among the various implementations, a roadmap for the new implementation, development of reusable implementations can be addressed. Accordingly, there is a requirement of a generic framework that can characterize the general methodology followed by any of the botnet detection methods. This paper, review various prevalent methods of botnet detection to extract commonalities among them. A global model for the detection of botnets is represented as ontology. Ontology is used as a means of knowledge representation. The botnet ontology is represented using Web Ontology Language (OWL). OWL is used because it is a language with layered architecture and high expressive power.